Where is caring in our nursing curriculum? - Rudolf Cymorr Kirby Martinez (San Beda University, 2021)
This editorial presents the current concern on situating caring as a grounding for curriculum among the helping professions. The context of the discipline of nursing and its curriculum in the Philippines was presented as an exemplar for discussion.